The complex social, cultural and psychological drivers of the ‘chemsex’ experiences of men who have sex with men: a systematic review and conceptual thematic synthesis of qualitative studies - Edward Mundy; Alexander Carter; Tom Nadarzynski; Christopher Whiteley; Richard O. de Visser; Carrie D. Llewellyn (Frontiers in Public Health)
IntroductionChemsex’ is the sexualised use of drugs among men who have sex with men (MSM). Past systematic reviews have primarily focussed on quantitative research exploring the key characteristics and health consequences of chemsex. However, a large body of qualitative literature exists, drawing on different theoretical frameworks.MethodsA systematic review and thematic synthesis of the qualitative research on chemsex was conducted with the aim of exploring the chemsex experiences of MSM in the context of substance misuse and addictions, and to reviewing their underlying theoretical frameworks. Six databases were searched, and 43 papers were included in the review.ResultsThe thematic synthesis resulted in four key themes: ‘characterising chemsex’, ‘the context around chemsex’, ‘the chemsex experience’, and ‘harms, saying safe, and stopping chemsex’. Only nine papers explicitly drew on theoretical frameworks, which were broadly divided into two categories: those which drew on psychological theories, and those that framed chemsex as a social and cultural phenomenon.DiscussionThe results of the thematic synthesis add further understanding of the key characteristics of chemsex as well as some of the complex social and psychological drivers which may shape why people have chemsex. Finally, the review highlights the clinical implications and inherent complexities in providing clinical services for those reporting chemsex and the need for greater application of theory to advance our understanding of chemsex and continue to develop appropriate forms of therapeutic support.Systematic review registrationhttps://osf.io/j6k9r/.